Does the Tricolor Langur Truly Have a Specific Habitat in Danau Sentarum Landscape? An Analysis of The Preferences Habitat Using Maximum Entropy - Sutopo, Sutopo; Santoso, Nyoto; Mardiastuti, Ani; Mulyani, Yeni A (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
The tricolored langur (Presbytis cruciger) is not only geographically restricted but is also believed to strongly depend on specific habitat types, particularly wetland ecosystems in northern Borneo. Despite its limited range and potential vulnerability, no comprehensive habitat assessment has been conducted within its distribution area. This study aims to model the habitat suitability of P. cruciger in the Danau Sentarum landscape using environmental variables derived from direct encounter data collected between 2021 and 2023, and analyzed using MaxEnt. Habitat suitability modeling revealed that 95.94% (228,658 ha) of the total study area (238,329 ha) was classified as unsuitable habitat. The remaining areas were categorized as marginally suitable (7,080 ha), suitable (1,977 ha), and highly suitable (614 ha). Highly suitable areas are concentrated in peat swamp forests, riparian forests, and lowland secondary forests located within 1 km of lake edges, extending into the hilly zones of the Danau Sentarum landscape. Among the environmental predictors, land cover contributed the most to the model, though it showed low permutation importance. In contrast, proximity to fire hotspots demonstrated high permutation importance, indicating an avoidance behavior towards fire-prone areas. The species preferred elevations ranging from 100 to 200 meters above sea level, with 8–25% slopes, and proximity to swamp forest and lake ecosystems. These results highlight the species' strong association with wetland ecosystems and underscore the importance of conserving these habitats to ensure its survival.